The eyelid tumor in Yogyakarta, Indonesia - Agus Supartoto; Annisa Nurina Ayuningtyas; Banu Aji Dibyasakti; Purjanto Tepo Utomo; Datu Respatika; Muhammad Bayu Sasongko (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2019)
Many types of eyelid tumors may easily be diagnosed from a clinical point of view. However only a small number of large studies exist exploring the frequency of eyelid lesions from different regions. According to the epidemiology of various eyelid lesions happened in Yogyakarta Special Region, this study was aimed to investigate the prevalence of eyelid tumors in Yogyakarta Special Region. A total of 94 patients were enrolled in a descriptive study. The data were taken retrospectively from the medical record. All patients were diagnosed with eyelid tumors from January 2014 until December 2017 by histopathological examination. Among the subjects, 56 (59.6%) were male and 38 (40.4%) were female. There was no difference found in laterality (OD 46% vs OS 50%). Sebaceous carcinoma was found in 15 (16%) patients, followed by squamous cell carcinoma (SCC) 13 (13.8%), basal cell carcinoma (BCC) 11 (11.7%), epidermoid cyst 7 (7.4%), non-Hodgkin lymphoma 7 (7.4%), and others. We also found that 11 (11.7%) of patients showed an inflammation appearance only. The therapy was varied from extirpation and biopsy (39.4%), wide excision (27.7%), excision and biopsy (18.1%), exenteration (10.6%), and also anterior and lateral orbitotomy (2.1%) for each procedure. The eyelid tumor was found equally in the right and the left eye. Sebaceous carcinoma followed by SCC and BCC were the most common eyelid tumor found in this study. A further study is needed to determine the risk factor of each tumor.